Probing G-Quadruplexes Conformational Dynamics and Nano-Mechanical Interactions at the Single Molecule Level: Techniques and Perspectives - Marco Lamperti; Riccardo Rigo; Claudia Sissi; Luca Nardo (Photonics)
The analysis of nucleic acid structures, topologies, nano-mechanics and interactions with ligands and other biomacromolecules (most notably proteins) at the single molecule level has become a fundamental topic in molecular biophysics over the last two decades. Techniques such as molecular tweezers, single-molecule fluorescence resonance energy transfer, and atomic force microscopy have enabled us to disclose an unprecedented insight into the mechanisms governing gene replication, transcription and regulation. In this minireview, we survey the main working principles and discuss technical caveats of the above techniques, using as a fil-rouge the history of their achievements in dissecting G-quadruplexes. The revised literature offers a clear example of the superior ability of single-molecule techniques with respect to ensemble techniques to unveil the structural and functional diversity of the several polymorphs corresponding to a single G-quadruplex folding sequence, thus shedding new light on the extreme complexity of these fascinating non-Watson–Crick structures.